Indication and Implantation Technique of Permanent Pacemaker - Cahyaningrum, Dwiana (ARKAVI [Arsip Kardiovaskular Indonesia], 2023)
Permanent pacemaker is effective therapy to handle heart rythm abnormalities (arrhytmia) such as AV Block, Sinus Node Dysfunction, and Fascicular Block. Permanent pacemaker has basic principles which is stimulating and pacing impuls from pulsation generator and delivered by lead to myocardium so the heart can depolarized properly. Implantation technique and choosing pacing mode on each device are different according to the indications that occur. As the development of technology creates medical innovation is a leadless pacemaker with advantages reduce complications that occur when device implantation compare to permanent pacemaker (conventional pacemaker).